A Multi-objective Gravitational Search Algorithm - Hassanzadeh, Hamid Reza; Rouhani, Modjtaba (2010 2nd International Conference on Computational Intelligence, Communication Systems and Networks, 2010)
Recently there has been a great research conducted on diverse variations of multi-objective swarm optimization algorithms each of which might have its own strengths and weaknesses. Due to the high complexity of multi-objective problems the efficiency of these methods has become a matter of concern. In this paper a new multi-objective meta-heuristic algorithm based on gravitational forces is proposed and applied to different test benches. The acquired results proved the superiority of the algorithm comparing with other pioneering techniques such as the MOPSO